Suprageneric phylogenetics of Myrteae, the generically richest tribe in Myrtaceae (Myrtales) - Lucas, E; Harris, S; Mazine, F; Bellsham, SR; Lughadha, E; Telford, A; Gasson, P; Chase, M (2007)
To clarify relationships within the predominantly Neotropical and exclusively fleshy-fruited Myrteae (49 genera and c. 2,500 species), we provide a phylogenetic hypothesis for evolutionary relationships between 31 of these genera by analyzing nuclear ITS and ETS ribosomal DNA, and plastid psbA-trnH and matK DNA sequences from 75 Myrteae species and 13 outgroup taxa using parsimony and Bayesian inference. Four morphological characters are epitomized on the resulting trees, and biogeographical analyses are also performed. Myrteae are monophyletic, comprising seven clades plus two isolated taxa of unclear relationships. Morphological characters exhibit homoplasy, although in combination are useful for clade diagnosis. Biogeographical analyses are inconclusive regarding the ancestral area of the tribe, but South American colonization before northern radiation via the Andes appears likely. The largest genera, Eugenia and Myrcia s.l., have western and southeastern South American origins, respectively.